Light‐Mediated Multi‐Level Flexible Copper Iodide Resistive Random Access Memory for Forming‐Free, Ultra‐Low Power Data Storage Application (Adv. Funct. Mater. 8/2023). (16th February 2023) - Mishra, Dhananjay; Mokurala, Krishnaiah; Kumar, Ajit; Seo, Seung Gi; Jo, Hyeon Bin; Jin, Sung Hun
Abstract : CuI‐Based Nonvolatile Memory In article number 2211022, Sung Hun Jin, and co‐workers explore the light mediated resistive switching of CuI based, resistive random‐access memory device in terms of the enhancement scheme for device reliability, current conduction and switching mechanism via low temperature study. This potentially opens a new paradigm for nonvolatile memory technologies with high density multibit data storage.